The analysis of biological diversity of coronaviruses contributes in the early awareness of their zoonotic spreading - Khaitovich, Aleksandr B.; Sataieva, Tatiana P.; Sheyko, Elena A.; Zukow, Walery (Ecological Questions, 2021)
The recent outbreak of COVID-19 rose a new wave of interest to coronaviruses though the first coronaviruses were discovered in the first half of the 20th century. That time coronaviruses were considered as a quite serious veterinary problem but they were not believed to become highly dangerous for humans. However, such ideas were revised in 2002 when SARS-CoV was transferred to human population in the Southeast Asia assumably from the bats, and later in 2012 when natural focus of the MERS-CoV was discovered in the Arabian countries. Using PubMed, EMBASE, Scopus, and Google scholar, the authors searched for various research and review articles using the combination of terms “coronavirus, Coronaviridae, SARS-CoV, MERS-CoV, SARS-CoV-2, COVID-19, taxonomy”. Due to the increased interest a large number of new Coronaviridae family members was revealed in the first decades of the XXI century. Since then taxonomic structures of coronaviruses underwent significant changes. This review is focused on the need for continued monitoring of the biological diversity of coronaviruses. The structural studies of coronaviruses regardless of the host species may allow us to identify early changes that can affect the evolutionary drift process of a particular HCoV species involved in viral transmission from bats or birds to humans. Taking into account the migratory abilities of bats and especially birds, it is necessary to not only to include coronaviruses in the ecological monitoring programs, but also to expand the scope and depth of environmental and virological monitoring.